Peran Mediasi Kepuasan Kerja dalam Hubungan Work-Life Balance dan Adaptive performance pada Karyawan Coffee Shop Glukosa Group di Kota Madiun - Veronika Agustini Srimulyani; Dewi Trisha Wardani (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT UNIVERSITAS SAPTA MANDIRI, 2026)
Job satisfaction is a key factor in human resource management, yet the mechanism by which work-life balance shapes adaptive performance, particularly through the mediating role of job satisfaction, among coffee shop employees in Indonesia remains underexplored. This study aimed to analyze the effect of work-life balance on adaptive performance with job satisfaction as a mediating variable among employees of Glukosa Group coffee shops. A quantitative approach with a causality design with a total of 34 respondents who were willing to participate from the 68 permanent employees of the coffee shop. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression and the Sobel test using SPSS version 27. Job satisfaction also positively and significantly influenced adaptive performance. The Sobel test confirmed the significance of partial mediation of job satisfaction, as the direct and indirect effects of work-life balance on adaptive performance remained significant (in a one-way test) after job satisfaction was entered into the model. Work-life balance directly and indirectly influences adaptive performance through increased job satisfaction, so companies need to prioritize both work-life balance and job satisfaction to maintain employees' overall adaptability and performance